Implementing anaerobic speed reserve testing in the field: Validation of vVO2max prediction from 1500-m race performance in elite middle-distance runners - Sandford, G. N.; Rogers, S. A.; Sharma, A. P.; Kilding, A. E.; Ross, A.; Laursen, P. B. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Anaerobic speed reserve (ASR), defined as the speed range from velocity associated with maximal oxygen uptake (vVO2max) to maximal sprint speed, has recently been shown to be an important tool for middle-distance coaches to meet event surge demands and inform on the complexity of athlete profiles. To enable field application of ASR, the relationship between gun-to-tape 1500-m average speed (1500v) and the vVO2max for the determination of lower landmark of the ASR was assessed in elite middle-distance runners. Methods: A total of 8 national and 4 international middle-distance runners completed a laboratory-measured vVO2max assessment within 6 wk of a nonchampionship 1500-m gun-to-tape race. ASR was calculated using both laboratory-derived vVO2max (ASR-LAB) and 1500v (ASR-1500v), with maximal sprint speed measured using radar technology. Results: 1500v was on average +2.06 ± 1.03 km/h faster than vVO2max (moderate effect, very likely). ASR-LAB and ASR-1500v mean differences were -2.1 ± 1.5 km/h (large effect, very likely). 1500v showed an extremely large relationship with vVO2max, r = .90 ± .12 (most likely). Using this relationship, a linear-regression vVO2max-estimation equation was derived as vVO2max (km/h) = (1500v [km/h] - 14.921)/0.4266. Conclusions: A moderate difference was evident between 1500v and vVO2max in elite middle-distance runners. The present regression equation should be applied for an accurate field prediction of vVO2max from 1500-m gun-to-tape races. These findings have strong practical implications for coaches lacking access to a sports physiology laboratory who seek to monitor and profile middle-distance runners.